Reintegrating Ethics and Institutional Theories - Nielsen, Richard P. (Journal of business ethics, 2013)
Organizational ethics and institutional theories are extended by recovering Weberian and Pre-Weberian theorizing that emphasized the joining of ethics and institutional theories. Understanding how ethics and institutional systems influence each other can advance our understanding of the nature and causes of structural organizational ethics issues and help guide potential reforms. We consider the interplay of these elements during the recession of 2008–2009, highlighting how structural ethics problems may have to be addressed at the institutional levels and not solely the individual or organizational levels.